KERAGAAN VEGETATIF DAN GENERATIF TANAMAN UBI ALABIO DENGAN PENAMBAHAN BOKASHI ECENG GONDOK DI LAHAN RAWA LEBAK - Nurul Istiqomah; Nur Hafizah; Khairul Fuadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
Alabio’s yam (Dioscorea alata L.) is a potential carbohydrate source that can be developed to meet food needs, especially in swamps and in dry areas. The use of organic fertilizers is believed to bring more benefits to agricultural production. Bokashi water hyacinth is compost which contains humic acid which can increase seed germination, stimulate plant growth, increase soil fertility, increase yield and produce phytohormone compounds that can accelerate root growth. This study aims to (i) determine the effect of adding water hyacinth bokashi to vegetative and generative performance of alabio sweet potatoes on lebak swamp and (ii) to obtain the best dose of bokashi water hyacinth on vegetative and generative performance of sweet alabio on lebak swamp. This research was conducted in Sungai Tabukan Village, Sungai Tabukan Sub-District, Hulu Sungai Utara Regency from May to November 2018. This study used a single randomized block design (RBD). The factors studied were various doses of water hyacinth bokashi consisting of 4 levels of treatment, namely e0 = 0 kg, e1 = 1 kg, e2 = 2 kg and e3 = 3 kg. The results showed that the addition of water hyacinth bokashi had an effect on the vegetative performance of plants on plant height and number of leaves, not affecting the stem diameter. The e3 treatment (3 kg) is the best dose for the vegetative period of alabio’s yams. As for the generative performance, the addition of water hyacinth bokashi has no effect.